Neutralization of omicron subvariants and antigenic cartography following multiple COVID 19 vaccinations and repeated omicron non JN.1 or JN.1 infections - Nungruthai Suntronwong; Sitthichai Kanokudom; Thaneeya Duangchinda; Warangkana Chantima; Pattarakul Pakchotanon; Sirapa Klinfueng; Jiratchaya Puenpa; Thaksaporn Thatsanathorn; Nasamon Wanlapakorn; Yong Poovorawan (Scientific Reports)
Abstract The ongoing emergence of SARS-CoV-2 variants, combined with antigen exposures from different waves and vaccinations, poses challenges in updating COVID-19 vaccine antigens. We collected 206 sera from individuals with vaccination-only, hybrid immunity, and single or repeated omicron post-vaccination infections (PVIs), including non-JN.1 and JN.1, and evaluated neutralization against omicron BA.5, BA.2.75, BQ.1.1, XBB.1.16, XBB.1.5, and JN.1. Neutralizing antibodies exhibited a narrow breadth against BA.5 and BA.2.75 and failed to neutralize BQ.1.1 and XBB lineages after three to five doses of the ancestral monovalent vaccine. Hybrid immunity elicited higher neutralizing titers than vaccination alone, but titers remained relatively low. A single omicron PVI elicited lower neutralization titers to all variants compared to wild-type (WT), indicating immunological imprinting. Repeated omicron PVIs, particularly JN.1, slightly mitigated these effects by increasing broad neutralization responses to all variants, though not significantly. Antigenic mapping demonstrated that XBB lineages and JN.1 are antigenically distant from WT and also evaded antibodies induced by earlier omicron variants (BA.1–5) PVIs. However, repeated JN.1 PVIs shortened this antigenic distance, indicating broader neutralization across omicron variants. These findings highlight SARS-CoV-2 immunity following various antigen boosts and the impact of repeated omicron JN.1 exposure on broad immunity, informing future COVID-19 vaccination strategies.